Effects of pre-teaching and contextual guessing strategies on vocabulary achievement among Saudi EFL learners - Mukhtar, Hafsa Pir; Ruhil Amal, Azmuddin; Zuraina, Ali (Universiti Malaysia Pahang, 2025)
A crucial but difficult component of learning English for Saudi undergraduate students, who frequently use conventional, teacher-centered approaches, is expanding one's vocabulary. By comparing the efficacy of three instructional strategies, i.e. pre-teaching, contextual guessing, and a traditional (control) approach, this experimental study fills a major vacuum in the regional literature. In a pre-test/post-test design, thirty Saudi EFL students were randomized to one of the three groups. The results show a distinct hierarchy of efficacy. The pre-teaching approach significantly improved comprehension and retention while having a strong and outstanding effect on vocabulary achievement. on the other hand, although the contextual guessing method demonstrated a quantifiable advantage, it did not offer a statistically significant advantage over conventional teaching. These findings demonstrate the pedagogical benefits of explicit, proactive vocabulary training in EFL settings where language exposure is restricted. The study finds that while unguided contextual guessing may not be adequate, incorporating systematic pre-teaching into curricula can greatly maximize vocabulary acquisition. To improve lexical development in comparable EFL contexts, instructors and curriculum designers can benefit greatly from these important, empirically supported implications.